The New Apostolic Reformation: The critical reflections of the ecclesiology of Charles Peter Wagner - Kelebogile Resane (HTS Teologiese Studies/Theological Studies, 2016)
Charles Peter Wagner is a well-known missiologist and ecclesiologist of the latest era. He is the author, trainer and prayer warrior who founded the New Apostolic Reformation (NAR) that seeks to establish a fourth house. The NAR is a heterodox movement in Protestant Christianity sometimes known as the apostolic-prophetic movement, commonly associated with both the Pentecostal and Charismatic churches worldwide since the beginnings of the 1990s. Central to their theology is their locus of dogma that the task of the church, under the leadership of the apostles and prophets, is to take dominion of the earth within Christendom (distinct from Catholicism, Protestantism and Orthodox Christianity). The ekklesia is the people of God, whether they are gathered in their congregations on Sunday as the nuclear Church, or scattered in the workplace Monday through Saturday as the extended Church. The extended Church, just like the nuclear Church, is founded on apostles and prophets, but in the extended Church these are the different people who operate differently under a different rule book. It is these extended church leaders who will be most effective in transforming society. Workplace apostles are called to take dominion in business, government, arts and entertainment, media, family and education. Panoramically, Wagner’s ecclesiology, like mainstream evangelical ecclesiology, is trinitarian, communal, missiological and eschatological in nature and character. The weaknesses on his ecclesiology include the notions of polity based on fivefold ministries, balance of power and authority on church leadership, phenomenological approach to texts, exegetical shortcomings, and secular models in ecclesiastical governance.